2019
DOI: 10.3390/nu11071568
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Its Associated Early-Life Factors among Chinese and Spanish Adolescents: A Pilot Study

Abstract: Metabolic syndrome (MetS) is a growing problem worldwide in adolescents. This study compared two sample populations of young people in Spain and China, and analyzed the association of birth weight and breastfeeding duration with MetS. A cross-sectional study was conducted in adolescents (10–15 years old); 1150 Chinese and 976 Spanish adolescents. The variables analyzed were anthropometric characteristics, biochemical markers, and demographic characteristics using the same methodology and data collection protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 43 publications
4
29
1
1
Order By: Relevance
“…The prevalence of overweight and obesity is consistent with previous studies that stated the increase of overweight and obese children from 4.2% in 1990 up to 6.7% in 2010 [51,52]. In this sense, several databases and studies have estimated that overweight and obesity are up to 24% in Spain [22,49,[53][54][55]. Additionally, prior studies have noted the importance of the geographical position, and climate since the higher prevalence of overweight is more common in the Mediterranean countries [55].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The prevalence of overweight and obesity is consistent with previous studies that stated the increase of overweight and obese children from 4.2% in 1990 up to 6.7% in 2010 [51,52]. In this sense, several databases and studies have estimated that overweight and obesity are up to 24% in Spain [22,49,[53][54][55]. Additionally, prior studies have noted the importance of the geographical position, and climate since the higher prevalence of overweight is more common in the Mediterranean countries [55].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, a previous study carried out by Wang et al in 2019 showed that MetS prevalence was around 2.5% in a population of Spanish adolescents [22]. Furthermore, this study and other studies showed that there are gender differences in the prevalence of MetS, being more prevalent in men than women [22,23].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations